1983
DOI: 10.1159/000123494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microinjections of 5,7-Dihydroxytryptamine in the Suprachiasmatic Nuclei of the Rat on Serotonin Reuptake and the Circadian Variation of Corticosterone Levels

Abstract: The role of the 5-hydroxytryptamine (5-HT) terminals in the suprachiasmatic nucleus (SCN) in the production of the circadian variation of corticosterone secretion was investigated by lesioning the 5-HT inputs to the SCN with 5,7-di-hydroxytryptamine (5,7-DHT). Vehicle-injected animals showed a normal circadian variation of corticosterone levels. In contrast, the mean corticosterone levels of the 5,7-DHT-lesioned group were intermediate between control peak and trough values, and although the individual rats sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This is in agreement with previous work showing that treatments that increase or decrease 5-HT activity can induce phase shifts (Honma et al, 1979;Witz-Justice and Campbell, 1982;Williams et al, 1983;Smale et al, 1990). In addition, previous studies have demonstrated increased 5-HT activity in the SCN at night (Hery et al, 1982;Faradji et al, 1983;Ramirez et al, 1987).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with previous work showing that treatments that increase or decrease 5-HT activity can induce phase shifts (Honma et al, 1979;Witz-Justice and Campbell, 1982;Williams et al, 1983;Smale et al, 1990). In addition, previous studies have demonstrated increased 5-HT activity in the SCN at night (Hery et al, 1982;Faradji et al, 1983;Ramirez et al, 1987).…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies have suggested that this projection can modulate SCN clock functioning, although it is not essential for the clock to operate. Some studies found that raphe lesions or chemical treatments that deplete brain 5-HT levels decrease the amplitude (Block and Zucker, 1976; Kam and Moberg, 1977;Szafarczyk et al, 1979) or change the phase (Honma et al, 1979;Williams et al, 1983;Smale et al, 1990) of circadian rhythms, although other studies found these treatments to have no effect on circadian rhythms (Moore and Klein, 1974;Balestrery and Moberg, 1976). In addition, injections of a monoamine oxidase inhibitor or 5-HT uptake blocker, both of which increase 5-HT levels, can phase-shift circadian rhythms in vivo (Wirz-Justice and Campbell, 1982).…”
mentioning
confidence: 99%
“…The involvement of 5-HT fibres in the regulation of CRF neurons is further supported by the findings that restraint stress increases both binding at 5-HT 1A receptors in hippocampus (Mendelson & McEwen, 1991) and 5-HT turnover in the anterior hypothalamus (De Souza & Van Loon, 1986), that fenfluramine (McElroy et ai, 1984;Van de Kar et al, 1985), 5-HT (Leibowitz et al, 1989) and 5-HT agonists (Calogero et ai, 1990; Owens et al, 1990Owens et al, , 1991 stimulate corticosteroid secretion, and that injection of the selective neurotoxin 5,7-DHT into the raphe nuclei reduces the adrenocortical response to neurogenic stress (Feldman et al, 1984). More selectivelesions of 5-HT terminals, through injection of 5,7-DHT into the PVN, completely block the rise in plasma corticosterone on photic or electrical stimulation of the dorsal hippocampus (Feldman et al, 1987), while injection of 5,7-DHT in the suprachiasmatic nucleus alters the circadian variations of the HPA axis (Williams et al, 1983). Furthermore, fluoxetine, which inhibits 5-HT reuptake (Gibbs& , and dextrofenfluramine, which also stimulates 5-HT release from terminals (Guillaume, 1989), both increase CRF concentration in hypophyseal portal blood.…”
Section: Control Of the Activity Of Crf Neuronsmentioning
confidence: 99%
“…Circadian rhythms can be disrupted to varying degrees by 5-HT depletion via PCPA (Szafarczyk et al, 1979), by lesions of the midbrain raphe nuclei (Levine et al, 1986), or by localized chemical lesions of 5-HT-ergic terminals in the SCN (Williams et al, 1983). Circadian rhythms can be disrupted to varying degrees by 5-HT depletion via PCPA (Szafarczyk et al, 1979), by lesions of the midbrain raphe nuclei (Levine et al, 1986), or by localized chemical lesions of 5-HT-ergic terminals in the SCN (Williams et al, 1983).…”
mentioning
confidence: 99%